A Novel Preparation Method of (Ti,Zr,Nb,Mo,W)B2-SiC Composite Ceramic Based on Reactive Sintering of Pre-Alloyed Metals - Yufei Zu; Zi Wang; Hongliang Tian; Fan Wu; Lianshen Fu; Jixiang Dai; Jianjun Sha (Crystals, 2023)
High-entropy diboride-based (MeB2-based) ceramics are promising high-temperature structural materials because of their excellent mechanical properties, high-temperature stability, and oxidation resistance. In order to achieve low-temperature sintering of the high-entropy ceramics, a novel preparation method of high-entropy (Ti,Zr,Nb,Mo,W)B2-SiC ceramics based on reactive sintering of pre-alloyed solid-solution metals and nonmetals of Si, C, B4C was conducted in the current work. Mechanical alloying behavior of the mixed metal powders, as well as the phase composition, microstructure, mechanical properties, and oxidation behavior of the as-sintered MeB2-SiC ceramic were investigated. The XRD, SEM, and EPMA results indicated that the primary MeB2 solid-solution and SiC phases could be successfully formed during reactive sintering at a relatively low temperature of 1650 °C. The as-sintered MeB2-SiC ceramics had a high relative density of 97.8% and high mechanical properties (hardness of 19.74 ± 0.8 GPa, flexure strength of 533 ± 38 MPa, and fracture toughness of 6.01 ± 0.77 MPa·m1/2). Combining the oxidation behavior and microstructure evolution of the oxidation layer, a continuous and relatively dense MeOx-SiO2 oxidation layer was gradually formed and covered on the external surface, leading to decelerating oxidation behavior after an oxidation exposure time of 10 min.